Ethereum Blockchain Interconnectivity for Dynamic and Privacy-Preserving Access Control - Christian Delgado-von-Eitzen; Manuel Jose Fernandez-Iglesias; Luis Anido-Rifon; Martin Llamas-Nistal (IEEE Access)
This paper introduces a novel access control architecture based on a dual-blockchain model that separates access management from data storage to enhance security and scalability. The system enables users to submit access requests to a primary blockchain, where smart contracts dynamically verify permissions before retrieving data from a secondary, isolated blockchain. This design enforces fine-grained, account-level access control while preventing direct exposure of sensitive data. A proof of concept was implemented using Hyperledger YUI to interconnect Ethereum-based blockchains, demonstrating secure inter-chain communication and dynamic permission enforcement. The proposed solution addresses key limitations in existing blockchain infrastructures and offers a flexible, decentralized framework suitable for applications requiring robust data governance and regulatory compliance.